Living alone and alcohol-related mortality: a population-based cohort study from Finland. - Kimmo Herttua; Pekka Martikainen; Jussi Vahtera; Mika Kivimäki (PLoS Medicine)
Background Social isolation and living alone are increasingly common in industrialised countries. However, few studies have investigated the potential public health implications of this trend. We estimated the relative risk of death from alcohol-related causes among individuals living alone and determined whether this risk changed after a large reduction in alcohol prices. Methods and findings We conducted a population-based natural experimental study of a change in the price of alcohol that occurred because of new laws enacted in Finland in January and March of 2004, utilising national registers. The data are based on an 11% sample of the Finnish population aged 15-79 y supplemented with an oversample of deaths. The oversample covered 80% of all deaths during the periods January 1, 2000-December 31, 2003 (the four years immediately before the price reduction of alcohol), and January 1, 2004-December 31, 2007 (the four years immediately after the price reduction). Alcohol-related mortality was defined using both underlying and contributory causes of death. During the 8-y follow-up about 18,200 persons died due to alcohol-related causes. Among married or cohabiting people the increase in alcohol-related mortality was small or non-existing between the periods 2000-2003 and 2004-2007, whereas for those living alone, this increase was substantial, especially in men and women aged 50-69 y. For liver disease in men, the most common fatal alcohol-related disease, the age-adjusted risk ratio associated with living alone was 3.7 (95% confidence interval 3.3, 4.1) before and 4.9 (95% CI 4.4, 5.4) after the price reduction (p<0.001 for difference in risk ratios). In women, the corresponding risk ratios were 1.7 (95% CI 1.4, 2.1) and 2.4 (95% CI 2.0, 2.9), respectively (p ≤ 0.01). Living alone was also associated with other mortality from alcohol-related diseases (range of risk ratios 2.3 to 8.0) as well as deaths from accidents and violence with alcohol as a contributing cause (risk ratios between 2.1 and 4.7), both before and after the price reduction. Conclusions Living alone is associated with a substantially increased risk of alcohol-related mortality, irrespective of gender, socioeconomic status, or the specific cause of death. The greater availability of alcohol in Finland after legislation-instituted price reductions in the first three months of 2004 increased in particular the relative excess in fatal liver disease among individuals living alone.